The impact of transformational leadership on employee performance and organizational citizenship behavior - Hidayat, Wanda Gema Prasadio Akbar (Annals of Human Resource Management Research, 2025)
Purpose: This study investigates the influence of transformational leadership, organizational culture, and the implementation of paperless services on Organizational Citizenship Behavior (OCB) and employee performance within the Regional Financial and Asset Management Agency of East Java Province. Methodology: A quantitative approach was employed, involving 122 employees surveyed through a census sampling technique. Data were collected using Likert-scale questionnaires and validated with Pearson’s product-moment correlation, while reliability was tested with Cronbach’s Alpha. Structural Equation Modelling (SEM) using AMOS and SPSS 20.0 was applied to examine the relationships among variables. Results: The Findings indicate that transformational leadership, organizational culture, and paperless service implementation significantly and directly enhance OCB and employee performance. However, OCB does not act as a mediator between these factors and performance. The study confirms that strong leadership, a supportive culture, and digital transformation initiatives are critical to improving employee outcomes. Conclusions: The research highlights that employee performance can be optimized through leadership that inspires, organizational values that reinforce cooperation, and technology that streamlines services. OCB plays a direct role in strengthening performance but does not moderate the effects of the other variables. Limitations: This study was conducted within a single government agency, which may limit the generalizability of the findings. The exclusive focus on internal organizational variables may also overlook other external factors affecting employee performance. Contribution: This study contributes to developing human resource management literature in the public sector by examining how leadership style, organizational culture, and digital transformation initiatives such as paperless services impact employee performance and OCB.